2021
DOI: 10.3390/genes12101592
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of HSP90 Gene Family Reveals Involvement of HSP90, GRP94 and Not TRAP1 in Heat Stress Response in Chlamys farreri

Abstract: Heat shock proteins 90 (HSP90s) are a class of ubiquitous, highly conserved, and multi-functional molecular chaperones present in all living organisms. They assist protein folding processes to form functional proteins. In the present study, three HSP90 genes, CfHSP90, CfGRP94 and CfTRAP1, were successfully identified in the genome of Chlamys farreri. The length of CfHSP90, CfGRP94 and CfTRAP1 were 7211 bp, 26457 bp, and 28699 bp, each containing an open reading frame (ORF) of 2181 bp, 2397 bp, and 2181bp, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Particularly, the HSP90 class encompasses the heat shock proteins that are highly conserved and widely distributed in the cytoplasm, chloroplast, mitochondria, and endoplasmic reticulum, accounting for 1–2% of total cellular proteins. It exists mainly as a homodimer, containing a 12 kDa N-terminal domain of the ATP-binding site, the 35 kDa intermediate domain, and a 25 kDa C-terminal substrate-binding domain [ 13 , 14 ]. The HSP70 class is one of the most widely distributed and studied heat shock proteins, comprising of a 44 kDa N-terminal ATP binding domain (NBD), 15 kDa substrate binding domain, and about 10 kDa C-terminal domain [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the HSP90 class encompasses the heat shock proteins that are highly conserved and widely distributed in the cytoplasm, chloroplast, mitochondria, and endoplasmic reticulum, accounting for 1–2% of total cellular proteins. It exists mainly as a homodimer, containing a 12 kDa N-terminal domain of the ATP-binding site, the 35 kDa intermediate domain, and a 25 kDa C-terminal substrate-binding domain [ 13 , 14 ]. The HSP70 class is one of the most widely distributed and studied heat shock proteins, comprising of a 44 kDa N-terminal ATP binding domain (NBD), 15 kDa substrate binding domain, and about 10 kDa C-terminal domain [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, the cardiac performance investigations in scallops reported that, with the increase of ambient seawater temperature, the heart rate and heart amplitude of scallops increased gradually before Arrhenius break temperature, and the results of which generally supported our hypothesis [ 53 ], whereas obvious down-regulations occurred in Arg0193880.1 at nearly all time points during high-temperature stimulation, indicating that transcriptional function inhibition was blocked by some protein synthesis [ 101 ]. A similar phenomenon of gene family member tissue-specific and time-dependent expression was also observed in Mitogen-activated protein kinase ( MAPK ) [ 106 ] and HSP90 genes in Zhikong scallops [ 107 ], providing implications for flexible regulation of bivalve gene families in response to heat stress. Collectively, our results showed a significant and flexible regulation profile (up-/down-regulated, tissue-specific, time-dependent) of these AiPC4s and possibly suggested a strong adaptation model under temperature stress.…”
Section: Discussionmentioning
confidence: 79%
“…Heat shock proteins (HSPs) have been widely found to play an important role in protecting organisms from heat stress through combining heat shock factor 1 (HSF1) with heat shock elements (HSEs) to upregulate HSP90 [44,45]. Meanwhile, the expression of HSP90 is regulated by salinity, reduced oxygen level, food scarcity, and heavy metals [44][45][46]. Interestingly, according to earlier research, HSP90 expression showed a time and concentration dependence under stress conditions.…”
Section: Discussionmentioning
confidence: 99%